DETERMINATION OF THE WEIGHT OF FACTORS AFFECTING THE PHYSICAL AND MECHANICAL CHARACTERISTICS OF WARM ASPHALT CONCRETE MIXTURES - Mudrychenko Anatolii; Savenko Vyacheslav; Illiash Sergii; Honcharenko Valentyn (World Science, 2024)
The article examines the main factors that affect the physical and mechanical characteristics of warm asphalt concrete mixtures. When establishing the most important factors, the method of expert assessments was used. The general scheme of expert surveys included the following stages: selection of experts; formation of questions and compilation of questionnaires; work with experts; formation of rules for determining total scores based on the scores of individual experts; analysis and processing of expert assessments. The main technological and technical parameters were accepted as factors included in the survey. The selection of parameters is based on the analysis of literary sources, taking into account the requirements of national standards [1]. Based on the results of research, it was found that the most significant factors are the temperature of mixing the mixture during preparation, the quantitative content of the energy-saving additive and the amount of asphalt concrete crumb.